ChemInform Abstract: Crystal Structure of Tris(hydroxylammonium) Orthophosphate. Issue 5 (January 2016) - Leinemann, Malte; Jess, Inke; Boeckmann, Jan; Naether, Christian
Abstract: Single crystals of (H3 NOH)3 PO4 are formed from a 1:3 molar mixture of H3 PO4 and NH2 OH upon cooling.